0337 Insomniacs in Late Pregnancy are Clinically Depressed: Exploring the Role of Nocturnal Rumination. (12th April 2019) - Kalmbach, David A; Cuamatzi-Castelan, Andrea S; Tonnu, Christine V; Sangha, Roopina; O'Brien, Louise M; Swanson, Leslie M; Roth, Thomas; Drake, Christopher L
Abstract: Introduction: Depression afflicts 13% of pregnant women. Insomnia complaints often increase across pregnancy. As insomnia often triggers depression, women with insomnia in late pregnancy may be at high depression-risk. Cognitive-emotional dysregulation is thought to underlie both insomnia and depression. We proposed nocturnal rumination (negative repetitive thinking in bed at night) to be a key form of cognitive-emotional dysregulation linking these disorders. Methods: A cross-sectional analysis of women (29.6±4.7 years) in late pregnancy (gestational weeks 26-33) receiving prenatal OB care at a large Midwestern health system completed online surveys of insomnia, depression, and nocturnal rumination. This study was IRB-approved. Results: Of 163 women, 59.5% of women endorsed clinical insomnia. Women with insomnia reported greater depression than good sleepers (t=4.93, p<.001). A higher proportion of insomniacs were depressed (24.7%) compared to 4.5% of good sleepers (χ 2 =11.59, p<.001). Insomniacs also reported higher nocturnal rumination than good sleepers (t=6.59, p<.001). Importantly, nocturnal rumination appeared to amplify the depressogenicity of insomnia such that 36.1% of insomniacs with high rumination were depressed compared to just 5.6% of insomniacs with low rumination (χ 2 =27.20, p<.001). Indeed, ruminating insomniacs were at 26.51-fold greater odds for depression than good sleepers without rumination (p<.01). Pregnant women with insomnia or nocturnal ruminationalone were not at elevated depression-risk. Conclusion: Insomniacs in late pregnancy endorse high rates of depression. Nocturnal rumination may amplify depression-risk in these women. Assessing insomnia and stress in routine prenatal care may allow opportunity for prevention or early intervention of perinatal depression through the timely deployment of treatments improving sleep and stress management. Support (If Any): N/A